Effect of Species Composition on Growth and Yield in Mixed Beech-Coniferous Stands - Tudoran, Gheorghe Marian; Cicsa, Avram; Cicsa (Boroeanu; Dobre, Alexandru-Claudiu; Sparchez, Gheorghe (Forests, MDPI, MDPI AG, Grosspeteranlage 5, CH-4052 BASEL, SWITZERLAND, 2022)
Research Highlights: In mixed stands, competitive and supportive relationships occur between trees, illustrated by their dendrometric characteristics. Background and Objectives: We investigated the effect of species composition on growth and yield in mixed beech-coniferous stands in the Romanian Carpathians. Materials and Methods: We selected sites with similar trophicity levels, as determined by the site mapping method. Under the same site conditions, we generated models to determine, for each species (spruce, fir, and beech), the main parameters of the site index, including mean height, dominant height, standing volume yield, and mean annual volume increment for different compositional species proportions (p(sp)) and categories of proportions (i.e., low p(sp), between 10 and 50%, and high p(sp), ranging between 60 and 90%). Results: Overall, up to the age of 100 years, mixed stands with low p(sp) had enhanced tree height growth, characterized by mean values 2.2% higher for spruce and 4.8% higher for fir and beech. Dominant height showed similar values, regardless of p(sp). Mixed stands in which the p(sp) increased (i.e., p(sp) > 50) were more productive, with the mean yield differences at the age of 100 years ranging from +1.7% (for fir) to +3.8% (for spruce and beech), increasing to +6% at 140 years. Conclusions: When setting management targets, the management of mixed forests should be based on an understanding of the relationship between the site, species ecological requirements, and their yield potential. Mixed stands can influence individual tree growth and stand yield through p(sp).